Orientação de pais como estratégia de prevenção de problemas de comportamento infantis: revisão da literatura e proposta de intervenção segundo princípios da análise do comportamento - Abbud, Gabriella (2016)
Although several studies point out to the need of preventing behavioral problems in children, there are, in pertinent literature, few studies that have their focus on primary prevention of these problems, especially in Brazil. This paper presents: a review of literature on interventions with caregivers who had preventing behavioral problems in children as their goal; a critical analysis of this production and characterization of basic features that should be present in an effective and preventive behavior analytic intervention. Based on 34 descriptors, a search was conducted on the bases Science Direct and PsycINFO, which resulted in 274 articles. Subsequent analysis reduced this total to 37 articles, which are characterized, for the most part, by: describing risk factors inherent to the studied children; having conducted interventions in selective or indicated level; describing as major educational practices to be taught to caregivers the use of positive reinforcement and non-punitive procedures; being conducted in clinical setting; managing some measurement of follow-up; using the verbal report and direct observation as behavioral measure and employing group design. Based on the analysis of these studies, some important aspects to a prevention program are proposed, as regards the objectives, pre-intervention, procedures, consequences provided for parent participation and program evaluation. Finally, given a shortage of empirical research on primary prevention application programs was found, more researches on the subject are suggested